Development of Halal Culinary MSMEs Using the Business Model Canvas - Panji Ahmad Harahap, Anugerah; Imsar, Imsar; Nasution, Juliana (Jurnal Sains Sosio Humaniora, 2026)
This study aims to analyse the business model of Bakso Urat Juara Bandar Khalifah MSME using the Business Model Canvas (BMC) approach, examine the existing value proposition in shaping brand identity and customer experience, and formulate more effective business model development strategies. The study employed a qualitative approach, with data collected through interviews involving the business owner, business partners, and customers. The findings reveal that the existing business model has incorporated the nine elements of the Business Model Canvas. However, its implementation remains relatively simple and has not been optimally integrated. In terms of value proposition, the business predominantly emphasizes functional values, such as product quality and affordable pricing, while emotional and visual aspects, particularly outlet design, have not been maximized. This condition contributes to a weaker brand identity and less distinctive customer experience. Several development strategies are therefore proposed, including outlet design standardization, product innovation, and service quality enhancement. Consequently, business model development should not merely focus on increasing sales performance, but also on creating sustainable value and strengthening business competitiveness. These insights contribute for small food vendors to move beyond basic survival and focus on creating memorable brand spaces that secure long-term market loyalty.